Being a woman in abortion: a study in the light of existential phenomenology (Research, Society and Development, 2021)
Objective: Unveil the experience of the being-woman facing abortion. Methodology: This is a qualitative research approaching the existential phenomenology of Martin Heidegger. Carried out with ten women in Maceió – Alagoas. Testimonies were obtained through the phenomenological interview. Results: From the analysis of the interviews, four units of meaning emerged: Being a woman experiencing loss; Being a woman experiencing pain; Being a woman experiencing sadness for the loss, Being a woman experiencing fear for the other. Conclusion: This study allowed the verification of the need for strategies that go beyond the immediate care inherent to the obstetric complications of abortion. Interventions are necessary in the biopsychosocial aspects, and professionals are not responsible for attributing a value judgment, but for understanding what each woman experiences, as well as care based on an attitude of empathy and acceptance.